A new method for the synthesis of 4-aminobenzoic acid - an intermediate for the production of procaine - A. H. Halstian; O. P. Baula; H. V. Tarasenko (Zaporozhye State Medical University, 2022)
Procaine is one of the oldest local anesthetics used in medicine. When absorbed and entering the systemic circulation reduces the excitability of peripheral cholinoreactive systems. Has a blocking effect on the autonomic ganglia, reduces smooth muscle spasms, and reduces the excitability of the myocardium and motor areas of the cerebral cortex. It is synthesized by oxidizing 4-nitrotoluene to 4-nitrobenzoic acid, which is subsequently reacted with thionyl chloride, the resulting acid chloride is then esterified with 2-diethylaminoethanol to give nitrocaine. Finally, the nitro group is reduced by hydrogenation over a Raney nickel catalyst. The oxidation stage is characterized by the formation of toxic, difficult to dispose of wastewater, valuable mineral oxidants, or high temperatures and excess pressure, in the case of using oxygen as an oxidant. Therefore, the search for new environmentally friendly and low-temperature methods of obtaining 4-nitrobenzoic acid is an urgent task. The aim of the work is to study the products, conditions, and study kinetics of the reaction of ozone with 4-nitrotoluene in acetic acid solution to develop a new method for the synthesis of 4-nitrobenzoic acid. Materials and methods. The glacial acetic acid qualification "P. F. A." before use was purified by distillation under vacuum in the presence of potassium permanganate. Salts of metals of qualification "P. F. A." and potassium bromide qualification "Ch. P." were used without prior purification. A gas-phase gradient-free catalytic duck reactor was used for kinetic studies. The mixing of gas and liquid phases in the reactor was achieved by shaking the reactor at a speed that allowed it to work in the kinetic region. The kinetics of the reaction was studied by changing the concentration of ozone in the gas phase at the outlet of the reactor by spectrophotometric method on a spectrophotometer "SF-46 LOMO". Results. The products, conditions, and kinetics of ozone reaction with 4-nitrotoluene were studied. It was shown that at temperatures of 20-90 °C is mainly ozonolysis of the aromatic ring, and the total yield of oxidation products by methyl group does not exceed 24.2 %, among which identified in the early stages of 4-nitrobenzyl alcohol and 4-nitrobenzaldehyde, and at deeper - 4-nitrobenzoic acid. The introduction of cobalt (II) acetate into the catalyst system almost completely was prevented ozonolysis and the main reaction product is 4-nitrobenzoic acid with a yield of 86.5 %. The addition of potassium bromide to the solution reduced the concentration of the catalyst by seven times and increased the reaction rate and yield of 4-nitrobenzoic acid to 95.6 %. Conclusions. A new environmentally friendly, low-temperature method for the synthesis of 4-nitrobenzoic acid by conducting the process of ozonation of 4-nitrotoluene in a solution of glacial acetic acid in the presence of a mixed cobalt bromide catalyst was developed.